Peran Teknologi Dalam Pengembangan Keterampilan Membaca Siswa Kelas Kelas VIII SMPN 2 Bone - Iskandar Iskandar; Muhammad Dahlan; Ratnawati Ratnawati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explore the role of technology in developing the reading skills of class VIII students at SMPN 2 Bone. With rapid technological advances, education is experiencing a significant transformation, including in teaching and learning methods for reading. This study uses a qualitative approach with a case study method to understand the impact of using technology such as educational software, e-books, and interactive reading applications on students' reading abilities. Data was collected through classroom observations, interviews with teachers and students, and document analysis. The results showed that the use of technology significantly increased students' motivation and interest in reading, as well as improving their reading comprehension. Technology allows access to a variety of more interesting and interactive reading materials, which not only improve reading skills but also broaden students' horizons and knowledge. However, this research also found several challenges, such as limited technological infrastructure and the need for training for teachers to utilize technology effectively. In conclusion, technology has great potential in developing students' reading skills, as long as it is implemented with the right strategies and adequate support.